Enhancing Student Competency through Project-Based Learning in Chemistry Education: Insights from Vietnam - Hanh, Bui Thi; Anh, Bui Tuan; Nga, Pham Thanh; Tuan, Nguyen Ngoc; Ninh, Tran Trung (An Overview of Literature, Language and Education Research Vol. 7, 2024)
This chapter reviews published works in Vietnam on the use of project-based learning in chemistry teaching, including 26 articles, 20 doctoral theses and 2 books in the last ten years. Research results on applying PBL in chemistry teaching all show that this is a modern and effective teaching method for developing students' abilities. Project-based learning is a method, that promotes students' initiative and creativity, training cooperation and developing necessary skills of the 21st century. However, the application of project-based learning in teaching is not yet popular in Vietnam. According to surveys conducted by published articles and doctoral theses that focus on the theory of chemistry teaching, there are numerous reasons to explain this current state. Among them, three main reasons can be changed to widely implement project-based learning and improve the quality of chemistry education in Vietnam. First, teacher training is still slow to innovate; Second, students are not familiar with self-study and group work; Third, student assessment has faced numerous challenges. There needs to be changes in teacher training programs and adequate compensation to attract high-quality students to the education sector. Encouraging students to actively self-study, work in groups and innovate competency-based assessment will improve the effectiveness of project-based learning in chemistry education in Vietnam.